Computational modelling of creep and cyclic visco-plasticity damage of CSEF steels at elevated temperatures - Ragab, Raheeg (2024)
The change in the energy landscape has raised the need for new materials development and improved constitutive material modelling to support energy decarbonisation efforts. Among the emergent high-temperature materials, which have found increasing applications for boilers and turbine components in the power generation sector, are 9 12% Cr tempered martensitic Creep Strength Enhanced Ferritic (CSEF) steels. The present thesis deals with the computational modelling of creep and cyclic visco plasticity damage of CSEF steels (particularly Grade 91 and FV566 steels) under elevated temperatures. One of the key challenges concerning the creep performance of CSEF steels is related to the wide variability in the creep ductility of steel casts. Nonetheless, consideration of creep ductility in creep damage modelling of CSEF steels and the design of pressure parts operating at high temperatures has received little attention thus far. To address this challenge, a phenomenological ductility-based continuum damage mechanics model (CDM) was proposed in this study, which captures the influence of material creep ductility on creep damage and rupture lives. The model holds a key advantage over existing models in that it requires fewer material constants to be identified and calibrated. The proposed model was implemented into an ABAQUS user-defined subroutine to simulate the creep deformation and damage behaviour of CSEF steel weldment and to predict creep crack growth behaviour in Grade 91 vessels weldment. Uniaxial creep tests and feature-type cross-weld creep tests were utilized to calibrate the proposed model and identify the relevant creep damage properties for the weld constituents including the base metal (BM), weld metal (WM) and heat-affected zone (HAZ). The capability of the model was then examined through multi-axial notch bar creep tests and full-scale components tests. The proposed model not only demonstrated good predictive capabilities but also offered an improved understanding of creep failure behaviour in Grade 91 welded joints. Based on the modelling results, the highly localised stresses and stress triaxialities in the HAZ region of the weld were found to play a key role in the occurrence of ‘Type IV’ failure in Grade 91 steel welded structures. Since next-generation powerplants are expected to operate intermittently, a refined understanding of the cyclic deformation and damage mechanisms of tempered martensitic CSEF steels is crucial. One of the thesis's key aims is to examine important aspects of the high-temperature cyclic visco-plasticity behaviour. Specifically, it focuses on the ratcheting (cyclic creep) and constraint (multi-axiality) effects which have not been extensively studied for 12% Cr CSEF steels. To achieve this aim, a hybrid methodology is adopted comprising cyclic mechanical tests, microstructural characterisation and physically based cyclic visco-plasticity damage modelling. Within the experimental program, fully reversed, load-controlled uniaxial and multi axial saw-tooth (SWT) low-cycle fatigue tests were carried out on martensitic steel (FV566) at 600oC. The mechanical tests were complemented by detailed microstructural characterisation of the tested samples to unveil the key mechanisms contributing to the cyclic visco-plasticity damage in the FV566 steel at high temperatures. Regarding the computational work, an improved microstructure informed visco-plasticity modelling framework is introduced, which accounts for the softening mechanisms due to dislocation annihilation and lath coarsening. The developed model was embedded in a user material subroutine in ABAQUS and implemented to simulate the uniaxial and multi-axial ratcheting behaviour and the associated microstructural evolutions. The VP model reasonably predicted the ratcheting behaviour under load-controlled cycling. Moreover, under multi-axial stress states, the model was able to predict crack initiation at the notched bar root. Based on this investigation, the micromechanics origin of the softening was elucidated. Additionally, the micro-damage modelling results in conjunction with the physical characterisation offered an improved mechanistic understanding of notch constraint in multi-axial LCF tests. Accurate material properties determination is crucially important for reliable creep life assessment of CSEF steels. However, this can be challenging for the heat-affected zone of the weld, particularly when applying conventional (standard size) creep testing methods due to the small volume of material available for sampling. To overcome this challenge, small specimen creep testing techniques such as small punch creep tests have been proposed as alternative means of creep properties characterization. However, creep data conversion from such tests can be very complicated. This is particularly true for the SPCT which exhibits several non-linear deformation mechanisms such as friction, plasticity etc. As such, simplified empirical relations for the analysis of the SPCTs and data interpretation are often employed. However, such approaches lack theoretical underpinnings, thereby limiting the potential of the SPCT as a standardised material characterisation method. To address this limitation, a novel mechanistic-based model was proposed in this study for the first time, which describes creep deformation and damage in the SPCT. The theoretical framework was established based on the membrane stretching theory and continuum damage mechanics-based constitutive model. The accuracy of the proposed analytical model was verified using finite element analysis. The analytical solutions demonstrated excellent capabilities and advantages over the existing models. Further, the potential applications of the new model for creep properties determination of martensitic steels from SPCT data were demonstrated.